CO TEACHING METHOD TO IMPROVE STUDENTS’ SPEAKING ABILITY IN LEARNING ENGLISH - Veren Lim; Dwi Riyanti; Ikhsanudin (Universitas Muhammadiyah Makassar, 2025)
Speaking ability is crucial in English language education, particularly for junior high school students, because it impacts their future academic and professional success. This study focuses on seventh-grade students at SMP Santu Petrus Junior High School, who show varied English proficiency levels due to diverse educational backgrounds and limited internet access in rural areas. These students often struggle with low engagement and confidence in speaking English, lacking vocabulary and proper pronunciation. To address these challenges, this research investigates the implementation of co-teaching, where two or more teachers collaboratively instruct in a single classroom. This approach aims to enhance language education by combining teachers' unique skills and methods. Conducted as a Classroom Action Research (CAR) (Brown, 2004), the study involves pre-tests, post-tests, observations, and field notes to assess co-teaching's method improvement. Previous studies suggest co-teaching improves student participation, engagement, and language proficiency through differentiated instruction and dynamic learning environments. This study aims to confirm these findings and provide practical insights into co-teaching to boost the speaking abilities of seventh-grade students at SMP Santu Petrus. The expected outcome is increased student participation, confidence, and overall English speaking proficiency.